Dynamic transcriptome profiling toward understanding the development of the human embryonic heart during different Carnegie stages. Issue 24 (12th October 2020) - Meng, Zhuo; Wang, Jian; Peng, Jiayu; Zhou, Yue; Zhou, Shuang; Song, Wenting; Chen, Sun; Wang, Qingjie; Bai, Kai; Sun, Kun
Abstract : Transcriptional regulation participates in heart development. However, the transcriptomes of human embryonic hearts during Carnegie stage (CS)10–CS16 have not been elucidated. Here, we found marked changes in the morphology and transcriptome of the human embryonic heart from CS10 to CS11. At CS12–CS14, the embryonic heart undergoes hypoxia‐to‐aerobic transformation. At CS14–CS16, transcriptome functions were related to energy metabolism, regulation of cholesterol, and processes related to inorganic substances. Moreover, the transcriptomes of cardiac progenitor cells derived from human embryonic stem cells (hESCs) most overlapped with those of human embryonic hearts at CS10. Cardiomyocytes derived from hESCs considerably overlapped with embryonic hearts at CS14–CS16. Overall, these results provide a new perspective into the characteristics of human embryonic heart development. Abstract :